Experimental Study on the Effectiveness of Water Mist Extinguishing Systems for Protecting Paintings in Art Gallery Museums: Developing an Initial Methodological Model - Davide Berardi; Marta Galuppi; Mara Lombardi (Buildings, 2023)
Determining the input parameters for the calibration of a water mist extinguishing system in a compartment is important for the evaluation of the performance of the design. Although there is a lot of research on the use of water mist, it is still difficult understand the behavior of the system in terms of safety of people and protection of things. In this study, we aimed to conduct an experimental analysis to evaluate the effectiveness of water mist extinguishing systems in protecting paintings in art gallery museums. We compared onsite tests in a compartment of an art gallery and a numerical analysis carried out with Fire Dynamics Simulator (FDS). Numerical analysis using FDS included the water-cooling effect and the heat power in the simulated environment and the calibration for a model was found by reproducing the onsite results. The temperature trend was monitored as an essential parameter for the protection of the paintings. The study aimed to not only verify the effectiveness of the water mist system but also investigate the reproducibility of real-scale conditions through a simulated environment. The most important result obtained is the possibility of using a simulated environment instead of real-scale tests in order to test water mist capabilities.